2021
DOI: 10.1080/26904586.2021.1894303
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effectiveness of a blended vulnerable witness training for forensic interviewers

Abstract: The current study tested the effectiveness of a compact (18 hour) and blended (involving online and face-to-face components) training course, adapted from a previously evaluated course found to be successful in fostering long-term change in interviewing skill. The compact course was developed by trimming the previous course to only include learning activities that empirically demonstrated improvement of interviewing skills. There were 41 US forensic interviewers, with prior training experience, who took part i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The findings also demonstrated the capacity of the adapted training to sustain improved skills. As in a previous adaptation of Benson and Powell’s (2015) program in the United States (Lawrie et al, 2021), the Chilean-adapted training yielded long-lived evidence-based behavior—including open-ended question use—up to 21 months after training in controlled conditions, as predicted. Although the proportion levels of open-ended questions decreased in the long term in field interviews, they remained superior to the baseline levels showing long-term training effects for this fundamental skill (Powell, 2008).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The findings also demonstrated the capacity of the adapted training to sustain improved skills. As in a previous adaptation of Benson and Powell’s (2015) program in the United States (Lawrie et al, 2021), the Chilean-adapted training yielded long-lived evidence-based behavior—including open-ended question use—up to 21 months after training in controlled conditions, as predicted. Although the proportion levels of open-ended questions decreased in the long term in field interviews, they remained superior to the baseline levels showing long-term training effects for this fundamental skill (Powell, 2008).…”
Section: Discussionsupporting
confidence: 67%
“…So far, evaluation research has evidenced the relatively short-lived results of training programs for interviewers unless continuous supervision and feedback were provided (e.g., Lamb et al, 2002;Rischke et al, 2011). Only the training program evaluated by Benson and Powell (2015) and a reduced version of it (Lawrie et al, 2021) showed long-lasting results without posttraining components. Outcomes of the current evaluation replicate Benson and Powell's results in the Chilean context using a culturally adapted version of Spanish of the original program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the first three cohorts were part of an evaluation of the training program (i.e. all participants that had completed the training up to the time the evaluation was conducted; Lawrie, 2021).…”
Section: Participantsmentioning
confidence: 99%
“…Learners were trained in a six-module course on best practices in investigative interviewing and they had to meet a criterion level of performance to pass the course. Even though the learners were already practicing interviewers, an evaluation of the training demonstrated that it improved their skills pre-to post-training, including 9-24 months later for a small subsample of trainees (Lawrie et al, 2021). Research shows that peer reviewers must develop the underlying content knowledge before they can effectively evaluate it in others (Lai, 2016).…”
Section: Reviewers Need Knowledge Of the Reviewed Conceptsmentioning
confidence: 99%